Double Addition of Propargylzinc Reagents to Acylcyanohydrins and Cyanocarbonates. Issue 40 (25th October 2022) - Liu, Meng; Dwadnia, Nejib; Chevalier, Tony; Hemon‐Ribaud, Annie; Pearson‐Long, Morwenna S. M.; Boeda, Fabien; Bertus, Philippe
Abstract: An efficient and mild synthetic methodology of double addition of propargylzinc reagents onto acylcyanohydrins and cyanocarbonates has been developed. After optimization of reaction conditions, dipropargylic α, α‐disubstituted hydroxyamides and N ‐Boc‐protected amino alcohols have been straightforwardly prepared in good yields. The valorization of the so‐obtained compounds was undertaken by cobalt‐catalyzed [2+2+2] cycloaddition reactions to provide functionalized pyridine derivatives. Abstract : Two darts in the middle! This work reports the double addition of propargylzinc reagents to nitriles (acylcyanohydrins and cyanocarbonates). This methodology provides a straightforward access to dipropargylic α, α‐disubstituted hydroxyamides or N‐Boc‐protected amino alcohols which can be converted into functionalized pyridine derivatives after cobalt‐catalyzed [2+2+2] cycloaddition reactions involving nitriles.